Rancang Bangun Mesin Penyangrai Kopi dengan Pengaduk Berputar - Imam Sofi’i (Jurnal Ilmiah Teknik Pertanian - TekTan, 2014)
The roasting technique coffee bean was one of factor which influence quality powder coffee besides factor of raw material.   The roasting technique are include operator skill, mixing coffee bean in cylinder, air temperature in roasting’s cylinder,  heating source that is utilized, and activity after roasting.  The objective of this research is to make roasted machine of coffee bean with rotate mixer and test performance. Method is used by making roasted machine with cylinder made from stainless and rotate mixer from stainless strip spiral shape. In the top of cylinder fully equipped with covered and smokestack. Source of heat from elpiji stove.  The result of design was roasted machine coffee bean with dimension of length 92 cm, wide 62 cm and high 160 cm with ±40kg cylinder capacity.  Roasted machine component are beam, cylinder, mixer, side cover cylinder, inlet, outlet, top cover cylinder, anvil of stove and gearbox. Result of test showed that first test was 17,14  kg/jam capacity, second test was 24 kg/jam capacity and third test was 28.97 kg/jam capacity.  Rpm of mixer was 40 rpm and average fuel consumption 1.5 kg/jam. Keywords: roasted machine, spiral mixer